Deconstruction of Personal Subjectivity in a Totalitarian society in the film «Dau» (London Journal of Research In Humanities and Social Sciences, 2024)
This article examines the dramatic mechanisms of influence on a person’s value system, leading to the destruction of personal subjectivity in a totalitarian society, symbolically depicted in the “Dau” film series. The main conflict interaction in such circumstances lies in the collision of the generally accepted system of humanistic values and totalitarian ideology.
Keywords: Modeling.; techniques; javelin throwing; individualization; ideology; Violence; Values; axiology; drama; manipulation; totalitarianism; superman